2009
DOI: 10.1111/j.1745-4557.2009.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition Properties, Physicochemical Characteristics and Shelf Life of Whole Milk After Thermal and Thermo‐sonication Treatments

Abstract: Raw whole milk (RM) was pasteurized with heat-pasteurized milk (TT) and thermo-sonication (US) treatments. Batch pasteurization was used for TT and 36, 72, 108 PRACTICAL APPLICATIONSThermo-sonication (US) is an available method that can improve some sensorial and quality milk characteristics such as color and appearance, while at the same time, ultrasound pasteurizes the product. Minor changes in nutritional properties of milk (i.e., protein content) have been reported after US, 3 Corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 29 publications
9
40
0
11
Order By: Relevance
“…Studies have shown that the shelf life of milk could be extended by US treatment (Bermudez-Aguirre, Mawson, Versteeg & Barbosa-Canovas, 2009;Cameron, McMaster & Britz, 2009); it therefore offers an alternative technology to pasteurization. The fat globules in whole milk are substantially reduced in size after US treatment and these sizes can be markedly smaller than those obtained by conventional homogenization (Villamiel & de Jong, 2000;Wu, Hulbert & Mount, 2001;Vercet, Oria, Marquina, Crelier & Lopez-Buesa, 2002;Riener, Noci, Cronin, Morgan & Lyng, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the shelf life of milk could be extended by US treatment (Bermudez-Aguirre, Mawson, Versteeg & Barbosa-Canovas, 2009;Cameron, McMaster & Britz, 2009); it therefore offers an alternative technology to pasteurization. The fat globules in whole milk are substantially reduced in size after US treatment and these sizes can be markedly smaller than those obtained by conventional homogenization (Villamiel & de Jong, 2000;Wu, Hulbert & Mount, 2001;Vercet, Oria, Marquina, Crelier & Lopez-Buesa, 2002;Riener, Noci, Cronin, Morgan & Lyng, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thermo‐sonication seems to be a viable option for pasteurization of milk and inactivation of spoilage microorganisms and other bacteria such as L. innocua (Bermúdez‐Aguirre and Barbosa‐Cánovas 2008; Noci and others 2009), E. coli (Ugarte‐Romero and others 2006), S. enterica Serovar (Cabeza and others 2004), and Shigella boydii 18 IDPH (Ugarte‐Romero and others 2007). Also, sonication can be used as a hurdle in the inactivation of bacteria such as L. innocua in milk when combined with other technologies such as thermal treatment and pulsed electric fields (Noci and others 2009).…”
Section: Introductionmentioning
confidence: 99%
“…El ultrasonido se ha utilizado también en la pasteurización de la leche con resultados importantes; la leche muestra un mayor grado de homogenización, de color blanco, y una mejor estabilidad después del proceso. En este método, la pasteurización y homogeneización se completan en un solo paso (Bermúdez-Aguirre et al, 2009). …”
Section: Calidad Sensorial De Los Alimentosunclassified